(untitled) (Sir Salimullah Medical College Journal, 2026)
Background: Respiratory distress syndrome (RDS) remains a leading cause of morbidity and mortality among premature newborns. Along with CPAP support, surfactant replacement therapy plays a critical role in determining outcomes. This study aimed to compare outcomes between early and late surfactant administration among preterm infants (<34 weeks) with RDS. Methods: Sixty preterm neonates were enrolled and divided equally into early and late surfactant groups. Both groups were comparable in terms of gestational age, birth weight, sex distribution, and maternal comorbidities. Maternal risk factors and neonatal complications were analyzed to identify associations with survival outcomes. Results: Early surfactant administration was more frequent among inborn newborns (73.3% vs. 56.7%). Although sepsis, NEC, and PDA occurred in both groups, higher frequencies of sepsis (56.7% vs. 40%) and mortality (66.7% vs. 30%) were observed in the late surfactant group (p=0.009). The need for mechanical ventilation was significantly lower in the early therapy group (33.3% vs. 63.3%, p=0.038). Mortality was strongly associated with neonatal sepsis (p=0.001), NEC (p=0.019), PDA (p=0.009), and need for ventilation (p=0.006). Among maternal factors, gestational diabetes mellitus (GDM, p=0.002), premature rupture of membranes (PROM, p=0.007), chorioamnionitis (p=0.028), and pregnancy-induced hypertension (PIH, p=0.004) were significantly linked to newborn death. Logistic regression identified late surfactant administration (OR=0.165, 95% CI: 0.029–0.948), GDM (OR=0.147, 95% CI: 0.035–0.615), and PROM (OR=0.239, 95% CI: 0.061–0.930) as independent predictors of mortality. Conclusion: Early surfactant therapy significantly reduced mortality and ventilation requirements among premature newborns with RDS, underscoring the importance of timely intervention and optimal perinatal care. Sir Salimullah Med Coll J 2025; 33: 7-18